A transient-features-based diagnostic method of multi incipient cracks in pipeline systems. (October 2022) - Zhang, Boran; Wan, Wuyi
Abstract: Previously the hydraulic characteristics of intermittent leakage through in-pipe incipient cracks were revealed by experiment, and the corresponding numerical simulation model was established to find general features of the special phenomenon. In this study, further investigation on diagnosing the incipient cracks was carried out using numerical analysis based on the hydraulic transient features. In addition to the previously extracted relationships between in-pipe transient flow and crack characteristics, more features of interactions among multi-cracks and in-pipe turbulence were revealed. Based on the findings, a kind of Transient-features-based Diagnostic Method was proposed to detect and predict the location of incipient cracks. The precision of the prediction was validated to be most accurate for the downstream crack. Aided with anti-streamwise cyclic progressive repairing strategy, the proposed diagnostic method will realize a significant reduction of costs for pipeline maintenance compared to traditional ways. Highlights: Sensitivity of pressure fluctuations was studied under multi-cracks conditions. Transient-features-based diagnostic method was proposed to detect incipient cracks. Anti-streamwise cyclic progressive repairing strategy was proposed for application. The proposed method remarkably helps to reduce the costs for pipe maintenance.